(Online) manipulation: sometimes hidden, always careless. Issue 1 (2nd January 2022) - Klenk, Michael
Abstract : Ever-increasing numbers of human interactions with intelligent software agents, online and offline, and their increasing ability to influence humans have prompted a surge in attention toward the concept of (online) manipulation. Several scholars have argued that manipulative influence is always hidden. But manipulation is sometimes overt, and when this is acknowledged the distinction between manipulation and other forms of social influence becomes problematic. Therefore, we need a better conceptualisation of manipulation that allows it to be overt and yet clearly distinct from related concepts of social influence. I argue that manipulation is careless influence, show how this account helps to alleviate the shortcomings of the hidden influence view of manipulation, and derive implications for digital ethics.